2023
DOI: 10.1109/tits.2023.3263358
|View full text |Cite
|
Sign up to set email alerts
|

Beyond RMSE: Do Machine-Learned Models of Road User Interaction Produce Human-Like Behavior?

Abstract: This is a repository copy of Beyond RMSE: Do machine-learned models of road user interaction produce human-like behavior?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…However, it should be noted that also with respect to this type of modeling, our results highlight the complexity of underlying mechanisms and behavioral phenomena that need to be learned and tested for. There is a mounting argument in favor of thoroughly investigating machine-learned behavior ( 56 ), and recent analyses of machine-learned road user models have indeed shown that the standard approach of training these, to minimize deviation between model-predicted and human trajectories, is not guaranteed to yield human-like interaction behavior ( 57 , 58 ). The mechanistic insights we have presented here, as well our approach of explicitly targeting interaction phenomena to be accounted for, may guide work towards more cognitively and behaviorally informed machine learning, to capture the subtleties of interaction that matter to humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that also with respect to this type of modeling, our results highlight the complexity of underlying mechanisms and behavioral phenomena that need to be learned and tested for. There is a mounting argument in favor of thoroughly investigating machine-learned behavior ( 56 ), and recent analyses of machine-learned road user models have indeed shown that the standard approach of training these, to minimize deviation between model-predicted and human trajectories, is not guaranteed to yield human-like interaction behavior ( 57 , 58 ). The mechanistic insights we have presented here, as well our approach of explicitly targeting interaction phenomena to be accounted for, may guide work towards more cognitively and behaviorally informed machine learning, to capture the subtleties of interaction that matter to humans.…”
Section: Discussionmentioning
confidence: 99%
“…More than one method was used to test the models prepared throughout the study. RMSE, a metric that was used to evaluate the accuracy of statistical predictions, was enacted in the initial testing processes [27]. RMSE was calculated as the square root of the mean square of the differences between the predicted values and the actual values (Equation ( 2)).…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…More than one method was utilized to test the models prepared within the scope of this study. The RMSE, a metric employed to evaluate the accuracy of statistical predictions, was used in the initial testing processes [33]. The RMSE is calculated as the square root of the mean square of the differences between the predicted values and the actual values (Equation ( 2)):…”
Section: Evaluation Metricsmentioning
confidence: 99%